Evolution of the atomic structure of a supercooled Zr55Cu35Al10 liquid. (March 2017) - Zhao, Jingfeng; Tang, Zheng; Kelton, K.F.; Liu, C.T.; Liaw, P.K.; Inoue, A.; Shen, Xiaoping; Pan, Shiyan; Johnson, M.L.; Chen, Guang; Fan, Cang
Abstract: Structural data from the supercooled Zr55 Cu35 Al10 ternary alloy liquid were collected in-situ in the temperature range from 1172 K to 953 K during continuous cooling using the high-energy synchrotron X-ray Advanced Photon Source. The lowest-r peaks of the pair distribution functions (PDFs) sharpened, becoming higher and narrower, with decreasing temperature. The experimental data are in good agreement with the results of ab-initio molecular dynamics (AIMD) simulations. Quantitative analyses of the simulated structures (clusters, interconnecting zones and free volume) in the supercooled liquid were made based on the tight-bond cluster model. The significance of Al additions on the increase in glass forming ability (GFA) was estimated from the simulated structures and their electronic structure analysis. Highlights: The structural data for Zr55 Cu35 Al10 supercooled liquid from the experiments and AIMD simulations matched well. Quantitative analyses of clusters, interconnecting zones and free volume were made based on the tight-bond cluster model. Density of states were calculated to probe the effect of different elements on the bonding properties.